2017
DOI: 10.1021/acs.joc.7b02588
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Activating Pd-Precatalyst for Suzuki–Miyaura and Buchwald–Hartwig Couplings of Aryl Esters

Abstract: Esters are valuable electrophiles for cross-coupling due to their ubiquity and ease of synthesis. However, harsh conditions are traditionally required for the effective cross-coupling of ester substrates. Utilizing a recently discovered precatalyst, Pd-catalyzed Suzuki-Miyaura and Buchwald-Hartwig reactions involving cleavage of the C(acyl)-O bond of aryl esters that proceed under mild conditions are reported. The Pd(II) precatalyst is highly active because it is reduced to the Pd(0) active species more rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 83 publications
1
41
0
1
Order By: Relevance
“…It is worthwhile to note that from amides 1a-1c,m ost syntheticallyu seful are amides 1c (N,N = Ph,Boc) due to ease of preparation from secondary benzamides in as ingle, operationally simple andh igh-yielding step. The observed order of reactivity with [Pd(IPr*)(cin)Cl] (1a> 1c> 1b)f ollows the reactivity order determined earlier using [Pd(IPr)(cin)Cl], [14] albeit at much lower conversions.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…It is worthwhile to note that from amides 1a-1c,m ost syntheticallyu seful are amides 1c (N,N = Ph,Boc) due to ease of preparation from secondary benzamides in as ingle, operationally simple andh igh-yielding step. The observed order of reactivity with [Pd(IPr*)(cin)Cl] (1a> 1c> 1b)f ollows the reactivity order determined earlier using [Pd(IPr)(cin)Cl], [14] albeit at much lower conversions.…”
Section: Resultssupporting
confidence: 81%
“…However,r ecent computational studies have shown that the more plausible pathway is the boronate one. Therefore, in this study,w eh ave only focused in the boronatep athway using potassium carbonate as ab ase in THF,c onditions employedb yt he Szostak group, [14] and potassium carbonate as ab ase (Figure 7). The transmetalation begins from intermediate I6 and the organoboronate compound.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations